The influence of the topographic position within highlands of Western Rwanda on the interactions between banana (Musa spp. AAAEA), parasitic nematodes and soil factors - Gaidashova, S.V.; Asten, Piet J.A. van; Delvaux, B.; Waele, D. de (Elsevier, 2010)
Soil properties vary according to the topography. They affect water uptake and root exploration in the soil. Consequently, they may also influence the spread of plant–parasitic nematodes. This study reports on the effect of toposequence-related variations in soil on banana yields, foliar nutrient status, and nematode impact. Twenty banana plots were visited within 6 hills/valleys at each of the three toposequence positions: valley bottom, mid-slope and crest. Important variability in plant growth, nutrition and soil properties was observed within the toposequence. Significantly better plant growth (height and girth) was observed in the valley bottoms, where banana bunch weight was 1.7–3.4 kg higher (although not significant) than at upper toposequence positions. Best plant growth was observed in valley bottoms in contrast to the highest N and K foliar deficiencies in this position. Plants in the valley bottoms had higher foliar Ca and Mg, and K compared to those in the crest. Plants in the mid-slope had greater percentage of dead roots (19.1%), compared to the plants in the valley bottoms (12.3%) and the crest (14.2%). Soils in the valley bottoms were deeper, sandier, with lower organic matter, lower N, and K compared to the soils at higher toposequence. Nematodes likely play a key role in banana root damage, however, their effect appear to be in relation to various soil factors at each position. The abundance of Pratylenchus goodeyi had generally limited impact on banana yields in fields having less than 5% slope (crest and valley bottom) where soil conditions were more optimal for root growth. However, in the presence of increased run-off on steeper middle slopes, root death was increased even under moderate pressure from P. goodeyi.